The notions of regulation and self-regulation in political science - Thomann, Eva (Journal of Self-Regulation and Regulation, 2017)
While political scientists concur about the increasing importance of regulation, the extant literature features a notable diversity of contemporary definitions of regulation. The various understandings of regulation put different emphasis on the role of the state and regulation as an instrument or a process, respectively. This article scrutinizes and clarifies the notions of regulation and self-regulation in the Political Science literature. Along three analytic questions – what is regulated, who regulates, and how is it being regulated? –, the essay illustrates developments from regulation as government intervention to regulation as governance and finally, regulation as various mechanisms of social control. The latter includes hybrid, private, transnational, voluntary and self-regulation. The article discusses the usefulness of modern notions of regulation, as well as potential future research trajectories. It concludes that there is a need for a conceptual consolidation that integrates different regulatory processes, actors and instruments and enables comparative, explanatory empirical assessments of regulatory impacts.
Gesehen am 07.09.2017